Silybin Alleviates Experimental Autoimmune Encephalomyelitis by Suppressing Dendritic Cell Activation and Th17 Cell Differentiation - Yang, Huan-Li; Shi, Xiao-Wu (Frontiers in Neurology, 2021)
Silybin, a peculiar flavonoid compound derived from the fruit and seeds of Silybum marianum, exhibits strong anti-inflammatory activities. In the present study, we found that silybin effectively alleviated experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), via inhibition of dendritic cell (DC) activation and Th17 cell differentiation. Silybin treatment greatly ameliorated the disease severity and significantly declined inflammation and demyelination of the central nervous system (CNS) of EAE mice. Consistent with the disease development, silybin-treated bone marrow-derived DCs (BM-DCs) exhibited reduced costimulatory molecules (e.g., CD80 and CD86) and MHC II expression. These results demonstrated the distinguished bioactivity of silybin for suppressing DC activation, inhibiting pathogenic Th17 inflammatory cell responses, and, eventually, alleviating EAE severity. Taken together, our results show that silybin has high potential for the development of a novel therapeutic agent for the treatment of autoimmune diseases such as MS.